Phase change trigger strengthening process of thermal insulation type ceramic fiber material

By uniformly introducing reinforcement into ceramic fibers and optimizing the phase change mechanism, the problem of insufficient improvement in the performance of thermally insulated ceramic fibers in the prior art is solved, and significant thermal insulation and insulation performance improvement in high temperature environments are achieved.

CN119162704AInactive Publication Date: 2024-12-20NANTONG ENPUR THERMAL ENERGY&TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411685473.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-23
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The phase change trigger strengthening process of existing insulating and insulating ceramic fiber materials cannot significantly improve their thermal insulation performance and insulation performance, especially in high-temperature and high-load working environments.

Method used

Ceramic fibers are prepared by mixing alumina powder, silicate powder, silica powder, zircon sand and hard clay clinker by weight. In addition, reinforcement agent is added to the ceramic fibers, and reinforcement agent is uniformly introduced through solution impregnation, melt blending or in-situ synthesis methods. The phase transformation mechanism of ceramic fibers is studied in combination with differential thermal analysis, thermogravimetric analysis and X-ray diffraction and other technologies, and the phase transformation mechanism of ceramic fibers is optimized. Structure and performance.

Benefits of technology

It significantly improves the thermal insulation performance and insulation performance of thermally insulated ceramic fiber materials, and can maintain lower temperatures and higher insulation values ​​at high temperatures, making it suitable for high temperature and high load application environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162704A_ABST
    Figure CN119162704A_ABST
Patent Text Reader

Abstract

The invention discloses a phase change trigger strengthening process of a heat insulation type ceramic fiber material, and relates to the technical field of phase change trigger strengthening process.The heat insulation type ceramic fiber material is prepared from, by weight, 22 parts of alumina powder, 17 parts of silicate powder, 11 parts of silica powder, 32 parts of zircon sand and 38 parts of hard clay clinker. The preparation method comprises the following steps: respectively pretreating raw materials, mixing the pretreated raw materials together through a mixer to form raw materials of the heat-insulating and insulating ceramic fiber material, and preparing the heat-insulating and insulating ceramic fiber material from the raw materials of the heat-insulating and insulating ceramic fiber material through one or more of a melt spinning method, a sol-gel method or a chemical vapor deposition method. The preparation method comprises the following steps: preparing ceramic fibers with required fiber diameters and fiber microstructures, shearing, compressing or winding the prepared ceramic fibers to endow the ceramic fibers with shapes and lengths, enabling the ceramic fibers to be rectangular or cylindrical, enabling the length of the ceramic fibers to be 140mm, and enabling the length of the ceramic fibers to be 140mm. And the diameter of the ceramic fiber is 3.5-4.8 m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase change triggered strengthening process, in particular to a phase change triggered strengthening process for a heat-insulating ceramic fiber material. Background Art

[0002] Thermal insulation ceramic fiber materials are materials with high thermal stability and good insulation properties, and are widely used in aerospace, energy, chemical and other fields. However, with the development of science and technology and the increase in application needs, traditional thermal insulation ceramic fiber materials have shown certain performance limitations in certain high temperature and high load working environments. In order to solve this problem, the phase change triggered strengthening process is introduced into the preparation process of thermal insulation ceramic fiber materials, but the thermal insulation and insulation properties of the existing thermal insulation ceramic fiber materials cannot be significantly improved.

[0003] The defects of the existing phase change triggered strengthening process of thermal insulation ceramic fiber materials are: 1. Patent document CN100494527C discloses a method for preparing phase-change energy storage fiber, "cellulose viscose solution is prepared by using cellulose pulp, and the solution is mixed with phase-change material paraffin melt to prepare spinning solution to spin phase-change energy storage viscose fiber. The functional fiber is mainly composed of cellulose and paraffin, wherein the paraffin content is 10-40% (relative to the weight content of cellulose). The method is used to prepare phase-change energy storage fiber, which has a simple process, effectively reduces the loss of phase-change material during fiber processing, and increases the content of phase-change material in the prepared fiber. The phase-change energy storage function of the phase-change energy storage fiber and the physical and mechanical properties of the fiber are excellent", but the thermal insulation performance and insulation performance of the existing thermal insulation ceramic fiber material cannot be significantly improved by the phase-change triggered strengthening process of the thermal insulation ceramic fiber material; 2. Patent document CN212247292U discloses a phase-change thermostatic fiber, which belongs to the field of material technology. It "includes a phase-change thermostatic fiber body and phase-change thermostatic microcapsules distributed in the phase-change thermostatic fiber body; the phase-change thermostatic microcapsules are core-shell structures, including an outer shell and a phase-change core wrapped in the outer shell; the average particle size of the phase-change thermostatic microcapsules is 1 μm; the material of the phase-change core is paraffin; the material of the outer shell is toluene-2,4 diisocyanate and hexamethylenediamine; the average particle size of the phase-change thermostatic microcapsules of the utility model is 1 μm, and the phase-change thermostatic microcapsules of this particle size can meet the process requirements of the spinning equipment, and the phase-change thermostatic microcapsules of this size can effectively prevent the agglomeration problem, ensuring the uniform distribution of the phase-change thermostatic microcapsules in the fiber", but the thermal insulation performance and insulation performance of the existing thermal insulation ceramic fiber materials cannot be significantly improved by the phase change triggered strengthening process of the thermal insulation ceramic fiber materials; 3. Patent document CN109678411B discloses a method for preparing a fiber-reinforced phase-change thermostatic board with high temperature control effect, which "comprises the following steps: (1) using graphite as a heat-conducting reinforcing phase and uniformly dispersing it in a molten phase-change material; (2) using a vacuum adsorption method to adsorb the above-mentioned phase-change material into expanded vermiculite to prepare a fixed phase-change material; (3) using fiber as a reinforcing phase and mixing it with cement, fixed phase-change material, water, and a water-reducing agent in a certain ratio to prepare a fiber-reinforced phase-change thermostatic board with high temperature control effect. Using fiber as a reinforcing phase The reinforcing phase doped into the phase change sheet effectively improves the mechanical properties of the sheet. The addition of graphite also effectively increases the thermal conductivity and improves the phase change response rate of the phase change material. With the increase in thermal conductivity, the phase change material inside the sheet undergoes a more effective phase change, thereby improving the temperature control effect. The raw materials used in this method are widely available and the operation process is simple, and phase change sheets with high temperature control effects can be prepared in large quantities. However, the existing phase change triggered strengthening process of thermal insulation ceramic fiber materials cannot significantly improve the thermal insulation and insulation properties of thermal insulation ceramic fiber materials; 4. Patent document CN107620212A discloses a method for preparing phase-change nanofibers. "The preparation method comprises the following steps: 1) pretreatment of nanofibers, 2) sufficient reaction, and 3) post-treatment of crude products. The preparation method of the present invention utilizes the hydroxyl activity of PEG and PVA-co-PE to graft the phase change material onto the PVA-co-PE nanofibers by condensation polymerization. The prepared phase-change nanofibers have a cross-linked network structure. Even during the phase change process, the fiber structure is relatively stable and not easily deformed. Therefore, there is no leakage or pollution." However, the thermal insulation and insulating properties of the existing thermal insulation ceramic fiber materials cannot be significantly improved by the phase change triggered strengthening process of the thermal insulation ceramic fiber materials. Summary of the invention

[0004] The purpose of the present invention is to provide a phase change triggered strengthening process for thermally insulating ceramic fiber materials to solve the technical problem that the thermal insulation and insulation properties of the thermally insulating ceramic fiber materials cannot be significantly improved by the phase change triggered strengthening process for thermally insulating ceramic fiber materials proposed in the above background technology.

[0005] To achieve the above object, the present invention provides the following technical solution: a phase change triggered strengthening process of thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 20 to 30 parts of alumina powder, 15 to 25 parts of silicate powder, 10 to 15 parts of silica powder, 30 to 40 parts of zircon sand, and 35 to 50 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the required fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 130-220 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism research: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1100℃~1300℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Test the thermal insulation and dielectric properties of the prepared ceramic fiber material.

[0006] Preferably, the raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after the impurities are removed, run the dryer for 15 to 20 minutes to dry, and mix the dried raw materials.

[0007] Preferably, the vacuum state is 13~15pa.

[0008] Preferably, the ratio of the reinforcing agent to the ceramic fiber is 1:50.

[0009] Preferably, the reinforcing agent is composed of the following parts by weight: 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder. The reinforcing agent is formed by stirring in a stirring kettle at a stirring temperature of 30 to 60° C. for 20 to 30 minutes.

[0010] Preferably, the ceramic fiber is added with the following weight portions of reinforcing material in an oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly in a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber.

[0011] Preferably, the size of the rubber powder is 5-8 μm.

[0012] Preferably, the ceramic fibers are prepared by arranging them in a grid-like manner to improve their tensile strength.

[0013] Preferably, the hard clay clinker is selected from clay clinker with a refractoriness of 1750-1780°C and an impurity content of 1%-1.8%.

[0014] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention comprises 22 parts of alumina powder, 17 parts of silicate powder, 11 parts of silica powder, 32 parts of zircon sand, and 38 parts of hard clay clinker, which are pretreated and mixed together by a mixer to form a raw material of a heat-insulating ceramic fiber material. The raw material of the heat-insulating ceramic fiber material is subjected to one or more of a melt spinning method, a sol-gel method, or a chemical vapor deposition method to prepare a ceramic fiber with a desired fiber diameter and a fiber microstructure. The prepared ceramic fiber is sheared, compressed, or wound by one or more of the methods to give the ceramic fiber a shape and a length. The shape of the ceramic fiber is one or more of a rectangle or a cylinder. The length of the ceramic fiber is 140 mm, and the diameter of the ceramic fiber is 3.5-4.8 μm. Phase change mechanism study: by differential thermal analysis (DS C) or thermogravimetric analysis (TGA) is used to analyze the phase change temperature and phase change enthalpy of the ceramic fiber during the heating process. The crystal structure change of the ceramic fiber during the phase change process is structurally analyzed using X-ray diffraction (XRD) or transmission electron microscopy (TEM). The analysis shows that the phase change mechanism temperature of the ceramic fiber is 1120°C. A reinforcing agent is added to the ceramic fiber, and the reinforcing agent is uniformly introduced into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis. The duration of uniform introduction of the reinforcing agent into the ceramic fiber is 22 minutes. The ceramic fiber is placed in an oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the oven is 22 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed for cooling to obtain a thermal insulation type ceramic fiber material. The thermal insulation and insulation properties of the prepared ceramic fiber material are tested. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is intended to test the present invention. DETAILED DESCRIPTION

[0016] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0017] In the description of the present invention, it should be noted that the terms "upper", "lower", "inner", "outer", "front end", "rear end", "two ends", "one end", "the other end" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance.

[0018] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "provided with", "connected", etc. should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0019] Example 1: Please refer to Figure 1 , an embodiment provided by the present invention: a phase change triggered strengthening process of a thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 22 parts of alumina powder, 17 parts of silicate powder, 11 parts of silica powder, 32 parts of zircon sand, and 38 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the desired fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 140 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism study: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1120℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, and the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 22 minutes; S5. Place the ceramic fiber in an oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the oven is 22 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed for cooling to obtain a heat-insulating ceramic fiber material. S6. Testing the thermal insulation and electrical insulation properties of the prepared ceramic fiber material; The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after removing impurities, run the dryer for 15 to 20 minutes to dry, mix the dried raw materials, the vacuum state is 13 to 15 pa, the ratio of the reinforcing agent to the ceramic fiber is 1:50, the reinforcing agent is composed of the following parts by weight, 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder, stir in a stirring tank, the stirring temperature of the stirring tank is 30 to 60 ° C, and stir The reinforcing agent is formed after the mixing kettle is stirred for 20 to 30 minutes. The ceramic fiber is added with the following weight portions of reinforcing materials in the oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly by a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber. The size of the rubber powder is 5 to 8 μm. When preparing the ceramic fiber, its tensile strength is improved by arranging it in a grid shape. The hard clay clinker uses a clay clinker with a refractoriness of 1750 to 1780°C and an impurity content of 1% to 1.8%.

[0020] Example 2: Please refer to Figure 1 , an embodiment provided by the present invention: a phase change triggered strengthening process of a thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 24 parts of alumina powder, 20 parts of silicate powder, 12 parts of silica powder, 34 parts of zircon sand, and 40 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the desired fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more thereof to give the ceramic fibers a shape and a length, wherein the shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 150 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism study: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1180℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Testing the thermal insulation and electrical insulation properties of the prepared ceramic fiber material; The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after removing impurities, run the dryer for 15 to 20 minutes to dry, mix the dried raw materials, the vacuum state is 13 to 15 pa, the ratio of the reinforcing agent to the ceramic fiber is 1:50, the reinforcing agent is composed of the following parts by weight, 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder, stir in a stirring tank, the stirring temperature of the stirring tank is 30 to 60 ° C, and stir The reinforcing agent is formed after the mixing kettle is stirred for 20 to 30 minutes. The ceramic fiber is added with the following weight portions of reinforcing materials in the oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly by a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber. The size of the rubber powder is 5 to 8 μm. When preparing the ceramic fiber, its tensile strength is improved by arranging it in a grid shape. The hard clay clinker uses a clay clinker with a refractoriness of 1750 to 1780°C and an impurity content of 1% to 1.8%.

[0021] Example 3: Please refer to Figure 1 , an embodiment provided by the present invention: a phase change triggered strengthening process of a thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 26 parts of alumina powder, 20 parts of silicate powder, 13 parts of silica powder, 36 parts of zircon sand, and 43 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the required fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 130-220 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism study: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1200℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Testing the thermal insulation and electrical insulation properties of the prepared ceramic fiber material; The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after removing impurities, run the dryer for 15 to 20 minutes to dry, mix the dried raw materials, the vacuum state is 13 to 15 pa, the ratio of the reinforcing agent to the ceramic fiber is 1:50, the reinforcing agent is composed of the following parts by weight, 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder, stir in a stirring tank, the stirring temperature of the stirring tank is 30 to 60 ° C, and stir The reinforcing agent is formed after the mixing kettle is stirred for 20 to 30 minutes. The ceramic fiber is added with the following weight portions of reinforcing materials in the oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly by a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber. The size of the rubber powder is 5 to 8 μm. When preparing the ceramic fiber, its tensile strength is improved by arranging it in a grid shape. The hard clay clinker uses a clay clinker with a refractoriness of 1750 to 1780°C and an impurity content of 1% to 1.8%.

[0022] Example 4: Please refer to Figure 1 , an embodiment provided by the present invention: a phase change triggered strengthening process of a thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 28 parts of alumina powder, 22 parts of silicate powder, 14 parts of silica powder, 38 parts of zircon sand, and 45 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the required fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 200 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism study: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1230℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Testing the thermal insulation and electrical insulation properties of the prepared ceramic fiber material; The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after removing impurities, run the dryer for 15 to 20 minutes to dry, mix the dried raw materials, the vacuum state is 13 to 15 pa, the ratio of the reinforcing agent to the ceramic fiber is 1:50, the reinforcing agent is composed of the following parts by weight, 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder, stir in a stirring tank, the stirring temperature of the stirring tank is 30 to 60 ° C, and stir The reinforcing agent is formed after the mixing kettle is stirred for 20 to 30 minutes. The ceramic fiber is added with the following weight portions of reinforcing materials in the oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly by a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber. The size of the rubber powder is 5 to 8 μm. When preparing the ceramic fiber, its tensile strength is improved by arranging it in a grid shape. The hard clay clinker uses a clay clinker with a refractoriness of 1750 to 1780°C and an impurity content of 1% to 1.8%.

[0023] Example 5: Please refer to Figure 1 , an embodiment provided by the present invention: a phase change triggered strengthening process of a thermal insulation ceramic fiber material, comprising the following steps; S1. By weight, 29 parts of alumina powder, 24 parts of silicate powder, 14 parts of silica powder, 39 parts of zircon sand, and 48 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the required fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 210 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism study: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1280℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Testing the thermal insulation and electrical insulation properties of the prepared ceramic fiber material; The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after removing impurities, run the dryer for 15 to 20 minutes to dry, mix the dried raw materials, the vacuum state is 13 to 15 pa, the ratio of the reinforcing agent to the ceramic fiber is 1:50, the reinforcing agent is composed of the following parts by weight, 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder, stir in a stirring tank, the stirring temperature of the stirring tank is 30 to 60 ° C, and stir The reinforcing agent is formed after the mixing kettle is stirred for 20 to 30 minutes. The ceramic fiber is added with the following weight portions of reinforcing materials in the oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly by a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber. The size of the rubber powder is 5 to 8 μm. When preparing the ceramic fiber, its tensile strength is improved by arranging it in a grid shape. The hard clay clinker uses a clay clinker with a refractoriness of 1750 to 1780°C and an impurity content of 1% to 1.8%.

[0024] Comparative experiment: The difference between the comparative example and embodiment 1 is that; By weight, 22 parts of alumina powder, 17 parts of silicate powder, 11 parts of silica powder, 32 parts of zircon sand, and 38 parts of hard clay clinker are pretreated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material. The raw material for thermal insulation ceramic fiber material is prepared by melt spinning, sol-gel or chemical vapor deposition to obtain ceramic fibers with a desired fiber diameter and fiber microstructure. The prepared ceramic fibers are sheared, compressed or wound to give them a shape and a length. The shape of the ceramic fibers is one or more of a rectangle or a cylinder. The length of the ceramic fibers is 140 mm and the diameter of the ceramic fibers is 3.5-4.8 µm. Phase change mechanism study: by differential thermal analysis (DSC) or thermogravimetric analysis Analysis (TGA) is used to analyze the phase change temperature and phase change enthalpy of the ceramic fiber during the heating process. The crystal structure change of the ceramic fiber during the phase change process is structurally analyzed using X-ray diffraction (XRD) or transmission electron microscopy (TEM). The analysis shows that the phase change mechanism temperature of the ceramic fiber is 1120°C. A reinforcing agent is added to the ceramic fiber, and the reinforcing agent is uniformly introduced into the ceramic fiber through solution impregnation, melt blending or in-situ synthesis. The duration of the reinforcing agent being uniformly introduced into the ceramic fiber is 22 minutes. The ceramic fiber is placed in an oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the oven is 22 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed for cooling to obtain a thermal insulation type ceramic fiber material. The thermal insulation and insulation properties of the prepared ceramic fiber material are tested.

[0025] The difference between the comparative example and Example 2 is that; In parts by weight, 24 parts of alumina powder, 20 parts of silicate powder, 12 parts of silica powder, 34 parts of zircon sand, and 40 parts of hard clay clinker are pretreated separately and then mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material. The raw material for thermal insulation ceramic fiber material is processed by melt spinning, sol-gel or chemical vapor deposition to prepare ceramic fibers with a desired fiber diameter and fiber microstructure. The prepared ceramic fibers are sheared, compressed or wound to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of a rectangle or a cylinder. The length of the ceramic fibers is 150 mm and the diameter of the ceramic fibers is 3.5-4.8 µm. Phase change mechanism study: by differential thermal analysis (DSC) or thermogravimetric analysis ( TGA), analyze the phase change temperature and phase change enthalpy of ceramic fiber during heating, use X-ray diffraction (XRD) or transmission electron microscopy (TEM) to analyze the crystal structure change of ceramic fiber during phase change, and the analysis shows that the phase change mechanism temperature of ceramic fiber is 1180℃, add reinforcing agent into ceramic fiber, and introduce reinforcing agent into ceramic fiber uniformly by solution impregnation, melt blending or in-situ synthesis method, and the duration of reinforcing agent uniformly introduced into ceramic fiber is 20-30 minutes, put ceramic fiber into oven for baking according to the phase change mechanism temperature of ceramic fiber, and the baking time of oven is 20-35 minutes for phase change, and the oven is in vacuum state, and ceramic fiber is taken out of oven and placed for cooling to obtain thermal insulation ceramic fiber material, and the thermal insulation and insulation properties of the obtained ceramic fiber material are tested.

[0026] The difference between the comparative example and embodiment 3 is that; By weight, 26 parts of alumina powder, 20 parts of silicate powder, 13 parts of silica powder, 36 parts of zircon sand, and 43 parts of hard clay clinker are pretreated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material. The raw material for thermal insulation ceramic fiber material is prepared by melt spinning, sol-gel or chemical vapor deposition to prepare ceramic fibers with desired fiber diameter and fiber microstructure. The prepared ceramic fibers are sheared, compressed or wound to give them a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical. The length of the ceramic fibers is 130-220 mm and the diameter of the ceramic fibers is 3.5-4.8 µm. Phase change mechanism study: by differential thermal analysis (DSC) or thermogravimetric analysis The phase change temperature and phase change enthalpy of the ceramic fiber during heating are analyzed by TGA. The crystal structure change during the phase change of the ceramic fiber is structurally analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The analysis shows that the phase change mechanism temperature of the ceramic fiber is 1200°C. A reinforcing agent is added to the ceramic fiber, and the reinforcing agent is uniformly introduced into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis. The duration of uniform introduction of the reinforcing agent into the ceramic fiber is 20 to 30 minutes. The ceramic fiber is placed in an oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed for cooling to obtain a thermal insulation type ceramic fiber material. The thermal insulation and insulation properties of the prepared ceramic fiber material are tested.

[0027] The difference between the comparative example and embodiment 4 is that; In parts by weight, 28 parts of alumina powder, 22 parts of silicate powder, 14 parts of silica powder, 38 parts of zircon sand, and 45 parts of hard clay clinker are pretreated separately and then mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material. The raw material for thermal insulation ceramic fiber material is processed by melt spinning, sol-gel or chemical vapor deposition to prepare ceramic fibers with desired fiber diameter and fiber microstructure. The prepared ceramic fibers are sheared, compressed or wound to give them a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical. The length of the ceramic fibers is 200 mm and the diameter of the ceramic fibers is 3.5-4.8 µm. Phase change mechanism study: by differential thermal analysis (DSC) or thermogravimetric analysis ( TGA), analyze the phase change temperature and phase change enthalpy of ceramic fiber during heating, use X-ray diffraction (XRD) or transmission electron microscopy (TEM) to analyze the crystal structure change of ceramic fiber during phase change, and the analysis shows that the phase change mechanism temperature of ceramic fiber is 1230℃, add reinforcing agent into ceramic fiber, and introduce reinforcing agent into ceramic fiber uniformly by solution impregnation, melt blending or in-situ synthesis method, and the duration of reinforcing agent uniformly introduced into ceramic fiber is 20-30 minutes, put ceramic fiber into oven for baking according to the phase change mechanism temperature of ceramic fiber, and the baking time of oven is 20-35 minutes for phase change, and the oven is in vacuum state, and ceramic fiber is taken out of oven and placed for cooling to obtain thermal insulation ceramic fiber material, and the thermal insulation and insulation properties of the obtained ceramic fiber material are tested.

[0028] The difference between the comparative example and embodiment 5 is that; By weight, 29 parts of alumina powder, 24 parts of silicate powder, 14 parts of silica powder, 39 parts of zircon sand, and 48 parts of hard clay clinker are pretreated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material. The raw material for thermal insulation ceramic fiber material is prepared by melt spinning, sol-gel or chemical vapor deposition to obtain ceramic fibers with a desired fiber diameter and fiber microstructure. The prepared ceramic fibers are sheared, compressed or wound to give them a shape and a length. The shape of the ceramic fibers is one or more of a rectangle or a cylinder. The length of the ceramic fibers is 210 mm and the diameter of the ceramic fibers is 3.5-4.8 µm. Phase change mechanism study: by differential thermal analysis (DSC) or thermogravimetric analysis ( TGA), analyze the phase change temperature and phase change enthalpy of ceramic fiber during heating, use X-ray diffraction (XRD) or transmission electron microscopy (TEM) to analyze the crystal structure change of ceramic fiber during phase change, and the analysis shows that the phase change mechanism temperature of ceramic fiber is 1280℃, add reinforcing agent into ceramic fiber, and introduce reinforcing agent into ceramic fiber uniformly by solution impregnation, melt blending or in-situ synthesis method, and the duration of reinforcing agent uniformly introduced into ceramic fiber is 20-30 minutes, put ceramic fiber into oven for baking according to the phase change mechanism temperature of ceramic fiber, and the baking time of oven is 20-35 minutes for phase change, and the oven is in vacuum state, and ceramic fiber is taken out of oven and placed for cooling to obtain thermal insulation ceramic fiber material, and the thermal insulation and insulation properties of the obtained ceramic fiber material are tested.

[0029] The thermal insulation ceramic fiber materials of Examples 1, 2, 3, 4 and 5 of the present invention and the existing thermal insulation ceramic fiber material (Comparative Example 1) were subjected to thermal insulation performance tests and insulation performance tests, respectively. The thermal insulation performance test was conducted at a temperature of 200 degrees for 10 minutes and then the values ​​were counted after standing for 5 minutes. The insulation performance test was conducted at a voltage of 220V. The values ​​were calculated and the results are shown in Table 1. Table 1:

[0030] From the data in Table 1, it can be seen that the temperatures after heating of the thermal insulating ceramic fiber materials in Examples 1, 2, 3, 4 and 5 of the present invention are 50, 48, 52, 46 and 54 respectively, which are significantly lower than the temperatures after heating of the thermal insulating ceramic fiber materials in Comparative Example 1. This indicates that the thermal insulation performance of the thermal insulating ceramic fiber materials of the present invention is significantly improved.

[0031] From the data in Table 1, it can be seen that the insulation values ​​of the thermally insulating ceramic fiber materials used in Examples 1, 2, 3, 4 and 5 of the present invention are 1.1, 1.01, 1.03, 1.2 and 1.05, respectively, which are significantly higher than the insulation value of the thermally insulating ceramic fiber material in Comparative Example 1. This indicates that the insulation performance of the thermally insulating ceramic fiber material of the present invention is significantly improved.

[0032] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A phase change triggered strengthening process for thermal insulation ceramic fiber materials. Features: The method comprises the following steps: S1. By weight, 20 to 30 parts of alumina powder, 15 to 25 parts of silicate powder, 10 to 15 parts of silica powder, 30 to 40 parts of zircon sand, and 35 to 50 parts of hard clay clinker are pre-treated and mixed together in a mixer to form a raw material for thermal insulation ceramic fiber material; S2. The raw material of the thermal insulation ceramic fiber material is subjected to one or more of melt spinning, sol-gel method or chemical vapor deposition method to prepare ceramic fibers with the required fiber diameter and fiber microstructure, and the prepared ceramic fibers are sheared, compressed or wound one or more of them to give the ceramic fibers a shape and a length. The shape of the ceramic fibers is one or more of rectangular or cylindrical, the length of the ceramic fibers is 130-220 mm, and the diameter of the ceramic fibers is 3.5-4.8 µm; S3. Phase change mechanism research: The phase change temperature and phase change enthalpy of ceramic fiber during heating are analyzed by differential thermal analysis (DSC) or thermogravimetric analysis (TGA). The crystal structure change during the phase change of ceramic fiber is analyzed by X-ray diffraction (XRD) or transmission electron microscopy (TEM). The phase change mechanism temperature of ceramic fiber is 1100℃~1300℃. S4, adding a reinforcing agent into the ceramic fiber, and uniformly introducing the reinforcing agent into the ceramic fiber by solution impregnation, melt blending or in-situ synthesis, wherein the duration of uniformly introducing the reinforcing agent into the ceramic fiber is 20 to 30 minutes; S5. Place the ceramic fiber in a baking oven for baking according to the phase change mechanism temperature of the ceramic fiber. The baking time of the baking oven is 20 to 35 minutes for phase change. The oven is in a vacuum state. The ceramic fiber is taken out of the oven and placed to cool to obtain a heat-insulating ceramic fiber material. S6. Test the thermal insulation and dielectric properties of the prepared ceramic fiber material.

2. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The raw material pretreatment is to put the raw material into a screening machine, run the screening machine for 10 to 15 minutes to remove impurities, put the raw material into a dryer after the impurities are removed, run the dryer for 15 to 20 minutes to dry, and mix the dried raw materials.

3. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The vacuum state is 13~15pa.

4. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The ratio of the reinforcing agent to the ceramic fiber is 1:

50.

5. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The reinforcing agent is composed of the following parts by weight: 10 to 20 parts of nanoparticles, 15 to 20 parts of whiskers, 20 to 35 parts of short fibers, 15 to 25 parts of water, and 10 to 15 parts of rubber powder. The reinforcing agent is formed by stirring in a stirring kettle at a stirring temperature of 30 to 60° C. for 20 to 30 minutes.

6. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The ceramic fiber is added with the following weight portions of reinforcing material in a baking oven: 5 to 10 parts of zirconium oxide and 8 to 15 parts of chromium oxide are stirred evenly in a mixer to form a reinforcing material. The reinforcing material interacts with the components in the ceramic fiber to form a more stable crystal structure, thereby improving the high temperature resistance of the ceramic fiber.

7. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 5, Features: The size of the rubber powder is 5-8 μm.

8. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The ceramic fibers are arranged in a grid-like manner during preparation to improve their tensile strength.

9. The phase change triggered strengthening process of the thermal insulation ceramic fiber material according to claim 1, Features: The hard clay clinker is selected from clay clinker with a refractoriness of 1750-1780°C and an impurity content of 1%-1.8%.

Citation Information

Patent Citations

  • Superfine ceramic fiber cotton and production method thereof

    CN113912384A

  • Friendly environmental porous ceramic panel for construction materials and preparation method thereof

    KR100889805B1

  • Manufacturing method of ceramic ware with high strength using the composite

    KR1020170077972A